Representation in Media Accessibility: On the Adoption of a Queer Feminist Perspective - Iturregui Gallardo, Gonzalo (Journal of Audiovisual Translation, 2023)
This article is a theoretical essay discussing the potential for the analysis of media accessibility contents and practices (AD, SDH, Sign Language Interpreting, etc.) through a queer feminist lens, which makes it possible to tackle the representation of diversity and non-normativity. Based on a literature review of previous works on the intersection of Queer and Feminist Studies, and Media Accessibility and Disability Studies, it shows the need for this approach based on the nature of media accessibility services, which primarily cater for people with disabilities, a historically excluded minority actively involved in the claim for socio-cultural space and representation. It then proposes a method of work and analysis that combines queer and feminist translation strategies – a method, which is subsequently applied to commercial instances of audio description of diversity. The conclusions highlight the need to bring accessibility closer to contemporary concerns in research, i.e., gender, queer, feminist, and postcolonial issues. Some future lines of research are proposed, such as the expansion of this model of analysis to other accessibility services or the call for interlinguistic studies. Lay summary This article presents theoretical essay which describes the potential of the analysis of media accessibility, those services for the visually impaired and the Deaf, such as audio description, subtitling and Sign Language Interpreting, through a queer feminist lens able to tackle the representation of non-normative characters and narratives: racialised or queer individuals, for instance. Based on a literature review that gathers previous works on Queer and Feminist Studies, and Media Accessibility and Disability Studies, it shows the need for this approach based on the nature of media accessibility services, which target people with disabilities, a minority actively involved in the claim for socio-cultural representation. It then proposes a method of work and analysis that combines queer and feminist translation strategies, which is subsequently applied to real excerpts of audio description of series. The conclusions highlight the need to bring accessibility closer to contemporary concerns in research, i.e. gender, queer, feminist, and postcolonial issues. Some future lines of research are proposed, such as the expansion of this model of analysis to other accessibility services or the call for studies combining different languages.